IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH PADA PELAJARAN IPAS SD DI GUGUS V KECAMATAN ABIANSEMAL - Jaya, I Ketut Manik Asta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
The learning process should be designed to stimulate students' critical thinking abilities, especially in addressing various contextual problems. This research aims to examine the implementation of problem-based learning models in the subject of Integrated Science (IPAS) in elementary schools in Gugus V, Abiansemal District. The significance of this research is to provide a detailed review of the stages of implementing problem-based learning models, from preparation to execution, and the challenges faced by elementary school teachers. This research is of a qualitative nature. The research subjects are fourth-grade students at SD Negeri 2 Abiansemal and SD Negeri 2 Blahkiuh, chosen through purposive sampling. Data sources for this research include observations, interviews, and literature reviews. Data analysis is conducted through data reduction, data presentation, and data summarization. The results of the implementation of the problem-based learning model can be seen in several stages: (1) the preparation stage involves preparing lesson plans and defining a set of problems that will serve as the starting point for discussing the subject matter. (2) In the implementation stage, teachers form student groups and guide them in working on problem-solving tasks. (3) During the evaluation stage, teachers not only assess students' work but also evaluate the problems as obstacles encountered by students during the learning process. In conclusion, elementary school teachers in Gugus V, Abiansemal District, have successfully implemented the problem-based learning model for the IPAS subject.